G22(P) Survey of Regional Paediatric Handover Practises – Are We Following the Guidelines?. (4th June 2013) - Thapliyal, R; Nath, P; Kelsall, W
Abstract : Background: With changing work patterns effective handovers are essential for patient safety and continuity of care. Handovers should be structured and follow good practise guidelines. Handovers should provide opportunities for educational activities, to initiate or complete work place based assessments (WPBA) and improve communication. The aim of this study was to review the practise in hospitals across the deanery. Methods: A 15-point online questionnaire was sent by email to all the trainees and tutors. The survey ran from June – September 2012. Results: 215 responses were received from 17 trusts (17/17 hospitals, 100%), 38% were from Consultants and 55% from trainees (58 ST1–3 and 63 ST4–8). Feedback covered all areas of paediatrics: 55% were from general paediatrics, 31% from neonatal intensive care and 10% from sub specialities and paediatric intensive care. 96% of respondents were involved in two or more handovers during their working day. 85% of the handovers were lead by consultants or registrars. All the handovers had registrars present, 95% had junior trainees, 89% consultants and 35% had members from nursing team. Majority (75%) of the handovers were presented by registrars/junior trainees with only 35% receiving any feedback. SBAR (Situation, Background, Assessment and Recommendation) method was only used for 42% of handovers. Majority (70%) of the handovers were conducted with the aid of printed sheets, which included: patient demographics (83%), presenting complaints (85%), investigations, results and treatment plans (83%). Only 11% of handovers were done electronically. Handovers had allocated start times (96%) with designated places (89%) close to area of work. However only 63% of the handovers started on time, 20% were free from distractions by allied professionals and just 5% were 'bleep' free. 68% had some educational activity within the time allocated in the handover. WPBAs were initiated or completed in only 11% of handovers. Overall 91% of trainees felt that the quality of handover was either average or good. Conclusions: The findings from our survey suggest that the quality of handovers is variable. Handovers should have a structured approach and free from distractions to ensure safety and continuity of care. Incorporating formal teaching and WPBA's could help develop the role of handovers.